2022
DOI: 10.3389/fvets.2022.866791
|View full text |Cite
|
Sign up to set email alerts
|

German Farmers' Awareness of Lameness in Their Dairy Herds

Abstract: Lameness is one of the most challenging problems in the dairy industry. Control is impeded because farmers often underestimate the number of lame cows. The objectives of this study were to assess German farmers' awareness of lameness in their herds and to determine the associations between farmers' awareness and their management practices, farm characteristics as well as with farmers' education, personality traits and attitudes. As a part of a large cross-sectional study, veterinarians visited farms in three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…For instance, in some of our previous focus group work (Ventura et al 2014 ) veterinarians, farmers and other dairy professionals identified lameness as a key welfare concern facing the dairy industry. However, the dairy sector continues to be challenged by the identification and treatment of lame cows in need of care (Jensen et al 2022 ), despite increasing attention to and awareness of lameness as a production and welfare challenge by dairy stakeholders (Wynands et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in some of our previous focus group work (Ventura et al 2014 ) veterinarians, farmers and other dairy professionals identified lameness as a key welfare concern facing the dairy industry. However, the dairy sector continues to be challenged by the identification and treatment of lame cows in need of care (Jensen et al 2022 ), despite increasing attention to and awareness of lameness as a production and welfare challenge by dairy stakeholders (Wynands et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Parity data were retrieved from DHI. A face-to-face, pen-and-pencil interview was conducted with the responsible farm manager as elaborated on by Jensen et al [ 40 ]. In brief, the attitude of the farmers towards their work on the farm was assessed and farmers rated their consent to each statement on a five-point Likert scale (“strongly disagree”, “disagree”, “neutral”, “agree”, “strongly agree”).…”
Section: Methodsmentioning
confidence: 99%
“…in Bayern (9,0–12,5%) 42 wegen dieser Ursache und den Lahmheitsprävalenzen von Kühen, die in Süddeutschland bei 23,2% lagen. In Ostdeutschland betrugen sie sogar 39,1% 43 . In einer anderen aktuellen Untersuchung lag die Lahmheitsprävalenz in ostdeutschen Großbetrieben, wenn ein – schon „veterinärmedizinisch behandlungswürdiger“ – Lahmheitsgrad von 3/5 zugrunde gelegt wurde, im Mittel bei 31,1% (21,8%–37,4%) 4 .…”
Section: Diskussionunclassified